Use of Turi Leaf Powder (Sesbania grandiflora) in Artificial Feed to Increase Growth and Survival of Gourami (Osphronemus gouramy) - Yuni Tri Dia Vega; Eka Indah Raharjo; Farida Farida (Central Research Institute For Agriculture, 2022)
This study aims to determine the best and appropriate percentage of turi leaf meal used in artificial feed compositions to increase the growth and survival of gourami, while the benefit of this study is as a source of information for fish farmers regarding the best percentage of turi leaf meal for growth and survival. live gourami. The research was conducted in October-December 2016 at the Fisheries Wet Laboratory, Muhammadiyah University, Pontianak, West Kalimantan. for 70 days, including 10 days of preparation of tools and materials and 60 days of research observation. This study used a completely randomized design (CRD) with 4 treatments and 3 replications. The treatment with the use of turi leaf flour is Treatment A: 0% turi leaf flour in feed (control), Treatment B: Turi leaf powder 15% in feed, Treatment C: Turi leaf powder 30% in feed and Treatment D: Turi leaf powder 45% in feed. Based on research results. Based on the results of research regarding the percentage of use of turi leaf flour that is the best and appropriate in the composition of artificial feed to increase the growth and survival of gourami which was carried out for 60 days, the following conclusions were obtained: (i) Treatment C with a percentage of use of turi leaf flour 30% gave the best specific weight and length growth values with each value of 3.80% and 3.40%. (ii) The best feed conversion value is found in treatment C, which is 2.56. (ii) The best survival value in treatment C is 86.67%. (vi) The best protein and fat retention values in treatment C were 33.91% and 39. 74% and the water quality parameter during observation was temperature 27-32°C pH ranged from 5.0-6.0. Dissolved oxygen is 4.0-5.0 ppm and NH3 ranges from 0.25-0.50 ppm.